USM GIVES PRIORITY TO STUDENTS WHO ARE KEEN ON SUSTAINABILITY ISSUES - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
TAIPING, 28 July 2015 Universiti Sains Malaysia (USM) does not merely look at excellent academic results in the selection of its students, but also it is based on having a deep interest in other aspects which include leadership and the ability to be an agent of change.